Principles of formation of individual signs of style in modern design graphics (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article discusses the principles of the formation of individual style features in modern project graphics. The main method for solving this problem is to explain the role of architectural drawing as an additional reflection of the ideas of the author's project, explain the importance of hand and computer graphics as a special creative and technical process in separate projects. The author draws attention to the fact that hand-drawn graphics are special, especially the original image, which is inherent only to one person. We can still vividly imagine the combination of the process of the human brain with pencil and paper, which give individual handwriting and life. It is argued that training and education are necessary for the formation of an individual style. Modern successors of this and specialists in didactic practice have developed and are developing new methods of correct representation, which greatly simplify and contribute to the development of this individuality. Therefore, pedagogical experience is also important for the formation of an individual sign of style in modern design graphics.Additional roles of entourage and staffage in the design process form a special vibration and experience in the formation of an individual style. They, in addition to the main style of presentation, allow you to create the desired symbiosis with a dry computer presentation and more lively and emotional hand-drawn graphics.It was advisable to apply the fact that the knowledge of various authors of graphic developments and drawings about understanding the basic principles and methods of graphic representation of the environment, the most important object, on the basis of which any future artist will create a unique drawing style, his own unique handwriting. The forms of graphic works can change over time for one author, under the influence of general changes in society, the emergence of new technologies, new tasks, etc.
Keywords: formation of an individual style; entourage; staffage; architectural graphics; hand-drawn graphics; computer graphics